Mother-Child Interactions at Six Months Postpartum are Not Predicted by Maternal Histories of Abuse and Neglect or Maltreatment Type - Sexton, Minden B. (Psychol Trauma, 2017)
OBJECTIVE: A history of childhood maltreatment (CM) is associated with increased rates of maternal psychiatric symptoms and other adverse outcomes in adulthood among postpartum women. However, to date only few studies examined associations between CM and mother-child interactions among a non-clinical sample of postpartum women and the specific potential influence of the type of abuse or neglect is poorly understood. This study aimed to examine the relationships between CM types and observed parenting in a non-clinical group of recently postpartum mothers with maltreatment histories. METHOD: Participants were 173 postpartum, non-clinically referred mothers oversampled in the community for CM histories (n=123, 72%) and their infants who underwent during a 6 months postpartum visit a high- and low-stress interactive task, which was video-taped for later independent coding on hostile, controlling and positive parenting. Mothers also provided information on demographics and type of CM (emotional, sexual, physical abuse and neglect). Differences of maternal parenting by history of CM and specific type were analyzed via two-way Univariate General Linear Models. RESULTS: Inconsistent with a priori hypotheses, no significant differences emerged between overall CM severity or exposure to any particular CM type and hostile, controlling, or positive parenting in the high or low-stress tasks. CONCLUSIONS: Findings suggest that non-clinical postpartum women with CM histories show resilience in regards to postpartum parenting quality and do not differentiate from non-CM maltreated postpartum mothers. We discuss the potential influence of resilience, moderating factors, clinical implications, and recommendations base on our findings.